The Septic Arthritis of the Temporomandibular Joint in a 6-year-old Boy: A Case Report - Irena Ivković; Martina Bukovac; Marin Štefančić; Andrijana Jović (Swiss Journal of Radiology and Nuclear Medicine)
Septic arthritis of the temporomandibular joint (TMJ) is an uncommon condition, particularly in pediatric patients. We present a case of a previously healthy 6-year-old boy who presented with septic arthritis of the TMJ with extra-articular involvement, which responded well to an extended course of intravenous antibiotic therapy, leading to complete resolution on follow-up imaging.